2013
DOI: 10.5455/ijmsph.2013.060920131
|View full text |Cite
|
Sign up to set email alerts
|

A study on Developmental delay among children less than 2 year attending Well Baby Clinic - Prevalence and antecedents factors

Abstract: Background: Early detection of neurodevelopmental abnormalities is important because of possibility of instituting early intervention program for that child. Trivandrum developmental screening test (TDSC) has sensitivity of 66.7% and specificity of 78.8%. This makes it a reasonably good test to screen children. Aims & Objective: To study the prevalence of developmental delay among children less than 2 years attending well baby clinic using TDSC and antecedents factors of developmental delay. Material and Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 9 publications
(5 reference statements)
0
10
1
Order By: Relevance
“…History of sepsis in developmentally delayed child was also mentioned by Meenai et al [2] in their study in Bhanpur, Bhopal. However, studies by Sachdeva et al [13] and Vora et al [12] contradict the association between neonatal jaundice and developmental delay observed in current study. However, in present study multiple gestation, period of gestation and birth asphyxia was not found to be significantly associated with global developmental delay which was supported and contradicted by several other studies across the world [2,12,13,16,17,20,21,23,24] .…”
Section: Socio-demographic Factorscontrasting
confidence: 80%
See 2 more Smart Citations
“…History of sepsis in developmentally delayed child was also mentioned by Meenai et al [2] in their study in Bhanpur, Bhopal. However, studies by Sachdeva et al [13] and Vora et al [12] contradict the association between neonatal jaundice and developmental delay observed in current study. However, in present study multiple gestation, period of gestation and birth asphyxia was not found to be significantly associated with global developmental delay which was supported and contradicted by several other studies across the world [2,12,13,16,17,20,21,23,24] .…”
Section: Socio-demographic Factorscontrasting
confidence: 80%
“…These findings were supported by several other studies conducted globally as well as in India [4,16,17,21,23] . A study by Vora et al [12] also revealed that sepsis was significantly associated with developmental domains of TDSC but no association was found with meningitis. History of sepsis in developmentally delayed child was also mentioned by Meenai et al [2] in their study in Bhanpur, Bhopal.…”
Section: Socio-demographic Factorsmentioning
confidence: 97%
See 1 more Smart Citation
“…A wide variation in the prevalence of DDs throughout the world ranging from 1.5% to 19.8% has been reported. (18)(19)(20) This could be attributed to the use of diverse tools for evaluating development, and studies being led in different societies. In the United States, the prevalence of any type of DDs is estimated at 15%.…”
Section: Discussionmentioning
confidence: 99%
“…4,8,9 A study conducted by Vora et al among children less than 2 years in well baby clinic with TDSC found prevalence of 9.5%. 4,10 Only mere assessment of developmental milestones of the children under RBSK will not help policy makers to take necessary action; various factors associated with the outcome should also be searched for taking measures. Any delay in development of children and its contributory factors may be suggestive of the need for strengthening the existing programs or the need for exploring and initiating newer possibilities.…”
Section: Introductionmentioning
confidence: 99%